Sugarcane growth and yields in response to long-term monoculture practices under different soil orders. Issue 1 (April 2021) - Kusumawati, A; Hanudin, E; Purwanto, B H; Nurudin, M
Abstract: Indonesia is the seventh largest sugar producer in the world. Monoculture sugarcane cultivation has been practiced since the Dutch era, especially in the Entisols, Inceptisols and Vertisols soil orders. The field research with this multilocation design aims to determine the effect of the monoculture sugarcane cultivation period (1–10, 11–20 and 21–30 years) on the growth and yield of sugarcane plants under the three soil orders. Analysis of variance (ANOVA) at a 5% significance and correlation was conducted to determine the effects of soil orders and monoculture period. The results showed that there were significant interactions between monoculture period and soil order on leaf fresh weight, leaf dry weight, root fresh weight, plant height, stalk diameters, number of stalks, leaf area, number of green leaf, root CEC, root length, root surface and root area. There was no interaction between monoculture period and soil order on stalk fresh weight, stalk dry weight, root dry weight, number of nodes. The sucrose content of sugarcane in Entisols at the 1–10 years monoculture period significantly lower (6.03%) compared to 11–20 years period (7.37%) and 21–30 year (7.79%), whereas at the 1–10 years monoculture period in Inceptisols and Vertisols (7.99% and 8.04 %) was significantly higher than that of Entisols (6.03%). Sugarcane productivity at monoculture period 1–10 years in Entisols significantly lowest (49.38 t/ha) compared to Inceptisols (54.82 t/ha) and Vertisols (63.05 t/ha) at the same period, while the 21–30 years period on Vertisols significantly highest (76.18 t/ha) compared to 11–20 years period (68.73 t/ha) and 1–10 years period (63.05 t/ha) in same soil order. These conditions indicate that the effect of long-term monoculture cultivation of sugarcane on the growth and yield of sugarcane varies, depending on the soil order as the grow medium and root parameters have the highest correlation with sugarcane yield. Land management to improve the root area is necessary for optimal plant growth.